What is the answer and how to work the problem

Hi Laura,

When you solve for a single variable in a simplified equation like this one you perform "reverse" operations (undue subtraction with addition and undue division with multiplication) on both sides of the equation until you've "isolated" the variable (which in this case is r). You also need to do the operations in the reverse order that you would if you were simplifying an expression.

In this case we start with:

-25 = r ÷ 3 - 11

First add 11 to both sides to cancel out the "-11":

-25 + 11 = r ÷ 3 - 11 +11 (11's on the right cancel)

-14 = r ÷ 3

Then multiply both sides by 4 to cancel out the "÷3"

-14 * 3 = r ÷ 3 * 3

-42 = r

So the answer appears to be -42. You can plug -42 in for r to double check your answer (if you want to be sure you made no mistake - always a good idea):

-25 = r ÷ 3 - 11 (now replace r with -42)

-25 = -42 ÷ 3 - 11 (when simplifying one side of the equation division comes before subtraction)

-25 = -14 - 11 = -14 + (-11) (now add -11 from -14)

-25 = -25

so you can see that when you substitute -42 for r your equation makes a true statement. This confirms your answer as:

r = -42